The impact of agomelatine and melatonin on human colorectal cancer: An in vitro investigation - Serhatlioglu, Ihsan (Annals of Medical Research, 2024)
Aim: Colorectal cancer (CRC) impacts almost one million people worldwide each year, with 500,000 deaths annually. In our country, CRC ranks as the third most prevalent cancer in women and the fourth in men. Melatonin, a hormone with well-established antioxidant and anti-cancer properties, is produced by the pineal gland. Agomelatine, used to antidepressant therapies, also acts on melatonin receptors and may offer therapeutic benefits in cancer treatment. This study investigates the effects of melatonin and agomelatine on the viability of human colorectal cancer cell lines (HCT-116 and Caco-2).Materials and Methods: HCT-116 and Caco-2 cell lines were treated with melatonin and Agomelatine, both dissolved in 96% ethanol, at doses of 0.1, 1, 5, and 10 mM for a duration of 24 hours. Cell viability was measured using 3-(4,5-dimetiltiazol-2-il)-2,5-difeniltetrazolyum bromide (MTT) assay. Statistical analyses were performed using IBM SPSS Statistics 24.0, applying Bonferroni correction and the Mann-Whitney U-test, with significance set at p
Keywords: Cancer; Melatonin; Agomelatine; HCT-116; Caco-2